A Critical Review of Agenda 2063: Prospects and Challenges for Africa’s Economic Renaissance - Opeyeoluwa, Rotimi Olajide; Fatokun, Samuel Olalekan (Journal of Contemporary International Relations and Diplomacy, 2022)
The paper examines the place and condition of Africa in the global economic index and the imperative to shift the narrative by way of changing course from the present sordid reality. The dominant absence of development in the continent remains a sore point which contemporary issues in a globalized world have further accentuated by reaffirming the continent as a laggard within the international political system. The study relied on secondary and tertiary sources for data. The study submits that despite the prospects for a more robust and sustainable contribution of the continent to the world economy, it has been unable to compete favourably in the global marketplace or even at the intra-states level within the continent because of the absence of the requisite political will and comprehensive road map to end the cycles of bad governance and economic crisis which has held the continent down for ages. Hence, this study calls on the African leaders to ensure that Agenda 2063 is vigorously implemented and thus making Africa both competitive and not falling into the tepidness which was the lot of previous continental initiatives.